Research hotspots in nutrition for patients with head and neck cancer from 2014 to 2024 - WANG Shuai, LIU Manfeng, AN Na, WANG Dikan, HUANG Qiuyu, LIN Zhumei (口腔疾病防治)
Objective To understand the current status, international cooperation, research hotspots, and development trends of nutritional studies on patients with head and neck cancer from 2014 to 2024, and to predict future research trends. Methods The Web of Science Core Collection database was searched to retrieve nutritional studies on patients with head and neck cancer from January 2014 to March 2024. The type of studies were “articles,” the language was English, CiteSpace 6.1 R6 software was used to conduct the bibliometric analysis, and the results were visualized to form a scientific knowledge map. Results A total of 1 528 documents were retrieved, with a linear increase in the number of annual publications. The country with the highest number of publications was the United States, and the institution with the highest number of publications was the University of Queensland, with closer collaboration between authors and institutions. The most frequently cited publication was a set of nutrition guidelines, and the highest-impact articles were mainly concerned with performing percutaneous endoscopic gastrostomy. Keyword analysis showed that quality of life, radiotherapy, and weight loss were the keywords of highest interest. The keyword cluster analysis resulted in 17 clusters, which were divided into five main categories: head and neck cancer, treatment, outcome results, intervention modalities, and rehabilitation. Body composition, enteral nutrition, and accelerated postoperative rehabilitation were persistent research hotspots. Keyword highlighting revealed that “enhanced recovery after surgery” has been the focus of research in the last two years, with “index” and “model” emerging as theme words. Conclusion The number of publications in the literature related to nutrition for patients with head and neck cancer has increased annually over the past 10 years. The research hotspots mainly focus on the quality of life and weight loss during radiotherapy, the content and application prospect of body composition assessment, different modes of nutritional support interventions and enteral nutritional tube feeding routes, and perioperative nutritional management in enhanced recovery after surgery. The potential clinical value of preoperative nutritional intervention under the concept of enhanced recovery and the construction of new types of nutritional index are the trends of future research.